A Comparative Bibliometric Analysis of Tax Compliance Research in Developed and Developing Countries (2014–2024) - Menno Bire, Mona Anjali Hana; Devano, Sony; Herdianty, Selly (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to conduct a comparative analysis of trends, collaborations, and research frameworks on tax compliance in developed and developing countries from 2014 to 2024. The research sample comprises 109 articles on tax compliance from developed countries and 758 from developing countries, identified in the Scopus database using the PRISMA approach. This study uses bibliometric analysis with the RStudio tool to identify the evolution of themes, author and institutional networks, and keyword visualisation and citation patterns. The results show that developed countries publish more articles on tax administration systems, governance stability, and economic structure analysis. In contrast, developing countries focus more on governance issues, corruption challenges, the information sector, and institutional capacity. In addition, there are disparities in the participation of developing countries in global research networks, including differences in topic emphasis and international collaboration. This study emphasises the importance of integrating qualitative and quantitative analysis to improve understanding of structural issues related to tax compliance and to inform future tax policy strategies.